Federal Contributions to Postsecondary Education Under the Established Programs Financing: Trends and Implications - Wu, Terry Yuk Shing (Canadian Journal of Higher Education, 1985)
This study reviews the federal funding of postsecondary education under the Established Programs Financing (EPF) arrangements introduced in 1977. Since 1977, federal transfers to the provinces for financing postsecondary education have increased in line with the growth rate of nominal gross national product, rather than in line with operating costs. This implies that the block funding arrangements have actually slowed the growth of federal contributions for the support of postsecondary education.